1999
DOI: 10.21273/hortsci.34.7.1263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Edible Fig `Bianco del Cilento' by Random Amplified Polymorphic DNA Analysis

Abstract: Random amplified polymorphic DNA (RAPD) analysis is currently used to estimate genetic relationships in plants. We have used RAPD analysis to distinguish six different cultivars of Ficus carica, and several of their clones, that are widespread in the Campania Region of Southern Italy. Among these cultivars, `Bianco del Cilento' has unique characteristics, and is particularly useful for drying and for the manufacture of syrups. The protection of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
(9 reference statements)
3
12
0
1
Order By: Relevance
“…The resulted level of intra-cultivar clonal similarity was very high and homogeneous, in agreement with Galderisi et al 17 In the same way, the 'Columbra Bianca' accessions showed very close similarity coefficients (NLc > 0.9). In particular, NLc = 0.96 for CBF 12 versus CBF 3D clone, NLc = 0.94 for CBF 3D versus CBF 9C and NLc = 0.93 for CBF 9C versus CBF 12.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The resulted level of intra-cultivar clonal similarity was very high and homogeneous, in agreement with Galderisi et al 17 In the same way, the 'Columbra Bianca' accessions showed very close similarity coefficients (NLc > 0.9). In particular, NLc = 0.96 for CBF 12 versus CBF 3D clone, NLc = 0.94 for CBF 3D versus CBF 9C and NLc = 0.93 for CBF 9C versus CBF 12.…”
Section: Resultssupporting
confidence: 90%
“…Previous works demonstrated that a low number of amplicons per primer was sufficient to produce useful fingerprints for cultivar and clone discrimination. 17,18 In particular, Galderisi et al 17 have reported that only two primers were sufficient to distinguish F carica cultivars. Figure 2 is an example of RAPD fingerprints, obtained using U1 primer on the nine reference cultivars, which demonstrate the cultivar diversity and the intra-variety homogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These genetic resources showed well differentiated phenotypes, while in some species such as fig the genetic variability was lowered by the high level of homozygosis. Similar results on local fig genetic resources were obtained in other areas of southern Italy (Galderisi et al 1999), as well as in four different areas in France (Khadari et al 1995).…”
Section: Discussionsupporting
confidence: 79%